2010
DOI: 10.1038/jhh.2010.44
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness and left-ventricular diastolic dysfunction: Guangzhou Biobank Cohort Study-CVD

Abstract: Brachial-ankle pulse wave velocity (baPWV), a marker of arterial stiffness, is an established cardiovascular risk factor of ventricular stiffening. We studied the association of baPWV with left-ventricular (LV) diastolic function in a sub-study of the Guangzhou Biobank Cohort Study. In all, 378 Chinese subjects with a normal ejection fraction (450%) had baPWV measurement by a noninvasive automatic waveform analyser, carotid intima-medial thickness (IMT) measurement by B-mode ultrasonography and cardiac diastol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 35 publications
2
16
2
Order By: Relevance
“…However, the relationships between indices of aortic stiffness and mild diastolic dysfunction, as defined by abnormalities in E/A (relaxation abnormalities), are less clear, with associations noted in some [15,23,26], but not other studies [19,21,27,29,30]. Moreover, the BP most strongly related to E/A or LVDD in some large studies is DBP rather than SBP [12,13,31,32].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the relationships between indices of aortic stiffness and mild diastolic dysfunction, as defined by abnormalities in E/A (relaxation abnormalities), are less clear, with associations noted in some [15,23,26], but not other studies [19,21,27,29,30]. Moreover, the BP most strongly related to E/A or LVDD in some large studies is DBP rather than SBP [12,13,31,32].…”
Section: Introductionmentioning
confidence: 90%
“…Indeed, a number of studies have demonstrated that increases in aortic stiffness, which are thought to mediate vascular-ventricular interactions, are associated with LVDD [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. It is therefore possible that increases in SBP, which more closely reflect aortic stiffness changes, are more important in mediating LVDD than increases in DBP.…”
Section: Introductionmentioning
confidence: 98%
“…The most striking result in our analysis was that hypertensive patients with reduced EF showed a closer relationship between arterial stiffness and LV function than hypertensive patients with preserved EF. Previous studies (Miyoshi et al 2011;Xu et al 2011) have demonstrated an association between arterial stiffness and LV diastolic dysfunction in patients with preserved EF, and suggested that increased arterial stiffness may be a causative factor of heart failure produced by LV diastolic dysfunction. Our data is in agreement with the association between arterial stiffness and LV diastolic dysfunction in hypertensives with preserved EF.…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic nervous activation induced by hypoxia resulting from apnea may be one of the mechanisms underlying the accelerated increase of the arterial stiffness in subjects with sleep apnea 34) . Although several cross- 46) , subclinical cerebral damage 47) , cognitive dysfunction 48) , renal dysfunction 49,50) , cardiac diastolic dysfunction 51) , left ventricular hypertrophy 52) , and/or increased carotid intima-media thickness 53) ].…”
Section: Metabolic Syndrome Sleep Apnea and Obesitymentioning
confidence: 99%